Poverty and primary schooling: field studies from Mumbai and Delhi - Banerji, Rukmini (2000)
A new and flexible approach to the schooling of children of the urban poor is imperative. Field studies in Mumbai and Delhi have yielded the insight that the reason for so many slum children not being in school has less to do with their families' economic circumstances than with the school system's shortcomings. The available evidence also suggests that the amount of learning the average slum family pupil in India acquires in primary school falls far short of what may legitimately be expected. - Reproduced
Keywords: Schools - India - Maharashtra; Schools - India - Delhi; Primary schools - India - Maharashtra; Primary schools - India - Delhi; Poverty - India - Delhi; Poverty - India - Maharashtra; Primary schools